1998
DOI: 10.1523/jneurosci.18-15-05901.1998
|View full text |Cite
|
Sign up to set email alerts
|

DOPA Decarboxylase Activity in Attention Deficit Hyperactivity Disorder Adults. A [Fluorine-18]Fluorodopa Positron Emission Tomographic Study

Abstract: Converging evidence implicates the dopaminergic system and the prefrontal and nigrostriatal regions in the pathophysiology of attention deficit hyperactivity disorder (ADHD). Using positron emission tomography (PET) with [fluorine-18]fluorodopa (F18-DOPA), we compared the integrity of the presynaptic dopaminergic function between 17 ADHD adults and 23 healthy controls. The ratio of the isotope concentration of specific regions to that of nonspecific regions reflects DOPA decarboxylase activity and dopamine sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
146
1
8

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(176 citation statements)
references
References 67 publications
(56 reference statements)
21
146
1
8
Order By: Relevance
“…Specifically, we aimed to address the following issues: (1) identify genetic susceptibility factors involved in ADHD in the serotoninergic neurotransmission system; (2) test the existence of common genetic factors in childhood and adulthood ADHD; and (3) 73 Interestingly, functional brain imaging studies showed evidence of altered DDC activity in children and adults with ADHD, also suggesting that DDC is a susceptibility factor common to both adulthood and childhood ADHD. 74,75 …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we aimed to address the following issues: (1) identify genetic susceptibility factors involved in ADHD in the serotoninergic neurotransmission system; (2) test the existence of common genetic factors in childhood and adulthood ADHD; and (3) 73 Interestingly, functional brain imaging studies showed evidence of altered DDC activity in children and adults with ADHD, also suggesting that DDC is a susceptibility factor common to both adulthood and childhood ADHD. 74,75 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, neuroimaging studies have consistently reported abnormalities in nigrostriatal dopaminergic brain structures (Aylward et al, 1996;Castellanos et al, 1996) and function (Zametkin et al, 1993;Vaidya et al, 1998;Zametkin and Liotta, 1998) in children with ADHD. Consistent with these findings, neuroimaging studies in ADHD adults have shown alterations in presynaptic dopamine storage processes (Ernst et al, 1998) and in the density of striatal dopamine transporters (DATs) (Dougherty et al, 1999;Krause et al, 2000Krause et al, , 2002, although not consistently.…”
Section: Introductionmentioning
confidence: 90%
“…Functional brain imaging studies (Ernst et al 1998;Ernst et al 1999) have reported increased DOPA decarboxylase activity in the midbrains of ADHD children and decreased activity in prefrontal regions in ADHD adults. The authors hypothesized that the increased subcortical activity was the primary abnormality.…”
Section: The Contribution Of Molecular Genetic Studies To a Dopamine mentioning
confidence: 99%
“…DOPA decarboxylase is an enzyme involved in the syn-thesis of dopamine, noradrenaline, and serotonin. Functional imaging studies have shown altered DOPA decarboxylase activity in the midbrain of children with ADHD and in prefrontal areas in ADHD adults (Ernst et al 1998;Ernst et al 1999). There has been no published data, however, regarding the potential role of the DOPA gene as a susceptibility locus in ADHD.…”
mentioning
confidence: 99%